2005
DOI: 10.1038/sj.bjc.6602585
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib treatment affects androgen levels in non-small-cell lung cancer patients

Abstract: Gefitinib, an inhibitor of the epidermal growth factor receptor (EGFR, HER1/ErbB1) tyrosine kinase, has been shown to have clinical activity against non-small-cell lung cancers (NSCLCs), especially in women nonsmokers with adenocarcinomas. The aim of the present study was to clarify the relationship between androgen levels and gefitinib treatment in patients with advanced NSCLCs. Sera from 67 cases (36 men and 31 women) were obtained pretreatment and during treatment with gefitinib monotherapy (days 14 -18) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Recent clinical data showed that non-small-cell lung cancer patients receiving gefitinib had significantly lower plasma concentrations of testosterone and dehydroepiandrosterone. Furthermore, nonsmoking women, a subgroup that has a higher response rate to gefitinib (19), had significantly lower dehydroepiandrosterone-sulfate in their plasma as compared with their (20). It is possible that these differences observed after gefitinib treatment were due to inhibitory effects on transporters expressed in humoral tissues secreting androgens.…”
Section: Discussionmentioning
confidence: 83%
“…Recent clinical data showed that non-small-cell lung cancer patients receiving gefitinib had significantly lower plasma concentrations of testosterone and dehydroepiandrosterone. Furthermore, nonsmoking women, a subgroup that has a higher response rate to gefitinib (19), had significantly lower dehydroepiandrosterone-sulfate in their plasma as compared with their (20). It is possible that these differences observed after gefitinib treatment were due to inhibitory effects on transporters expressed in humoral tissues secreting androgens.…”
Section: Discussionmentioning
confidence: 83%
“…Under normal conditions, both androgen (testosterone) and estrogens (estradiol, progesterone) are proposed to have beneficial effects to modulate lung structure and function (13). For example, androgen enhances the inhibition of immune response and stimulate the growth of lung tissue (21), whereas estrogens participate in the regulation of many pulmonary functions such as pulmonary vasodilation (17,19). We speculate that disorders of lung function as a result of lung tumorigenesis may be the reason for the reduced sex hormones in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, women who do not smoke are more susceptible to developing adenocarcinoma, a cancer type that derives from PTII cells expressing AR. Since epidermal growth factor receptor (EGFR) plays a major role in adenocarcinoma (Johnson and Jänne, 2005), it is interesting that an inhibitor of EGFR which is widely used to treat lung adenocarcinoma, gefitinib, has been shown to lower androgen levels especially in patients responding to treatment (Nishio et al, 2005). Our results show that some human lung cancers express AR, and a human alveolar carcinoma-derived cell line with PTII-like properties, A549, not only contains AR but also exhibits androgen-dependent gene expression.…”
Section: Ar and Lung Cancermentioning
confidence: 99%